Pengaruh Penggunaan Media Terhadap Hasil Kreatif Produksi Variety Show Mission X Trans TV - Rosiana Andhikasari (Universitas Bina Sarana Informatika, 2019)
Abstract - This study is aimed to investigate the effect of media uses towards the result of creative production of variety show Mission X Trans TV on resident of Perumahan Griya Permata Asri Tulungagung, East Java. Sub variable of media uses such as frequency, intensity, duration, media content, the individual’s relationship with media. Related literature used in this research is uses and gratification theory. This research belongs to quantitative research. Sample employed here is 78 resident of Perumahan Griya Permata Asri Tulungagung, East Java. In gathering the data, questionnaire is used and the result is counted by using likert scale. Moreover, to make the data valid, some tests are also used. They are validity test and reliability test. Furthermore, the data are analyzed by using double linier regression analysis. From the results of data analysis and discussion it was found that the variable of media uses (X), have a significant effect on creative production (Y). The contribution of media uses amounted to 45,7%, the remaining approximately influenced by other factors besides these variable. The existence of a good escapits needs effect of resident perceives the success of production team of Mission X Trans TV. To obtain a positive perception of the public, production team of Mission X Trans TV must improve the quality of program television. Keywords: media uses, creative production, variety show